Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1097/01.smj.0000141306.20265.1e
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of the Tumor Marker CA125 in Right Heart Failure

Abstract: Carbohydrate antigen 125, known as a marker for ovarian cancer, has been reported to be elevated in heart failure caused by left ventricular dysfunction. A case of elevated carbohydrate antigen 125 in isolated right heart failure due to atrial septal defect with preserved left ventricular function is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…In a different study by Yilmaz et al [5], elevated levels of CA 125 reflected right ventricle dysfunction in patients with COPD even before corpulmonale to be evident [5]. Our report adds to the literature a unique case that describe CA 125 elevation in a patient with isolated right heart failure in the setting of rheumatic heart disease [6,7]. Though the exact mechanism remains unclear, the production of CA 125 is hypothesized to be increased secretion by the peritoneal mesothelium, either via a direct stretch activation due to the as cites from the right heart failure or via an indirect activation through inflammatory cytokines such as interleukin-6 [8].…”
supporting
confidence: 54%
“…In a different study by Yilmaz et al [5], elevated levels of CA 125 reflected right ventricle dysfunction in patients with COPD even before corpulmonale to be evident [5]. Our report adds to the literature a unique case that describe CA 125 elevation in a patient with isolated right heart failure in the setting of rheumatic heart disease [6,7]. Though the exact mechanism remains unclear, the production of CA 125 is hypothesized to be increased secretion by the peritoneal mesothelium, either via a direct stretch activation due to the as cites from the right heart failure or via an indirect activation through inflammatory cytokines such as interleukin-6 [8].…”
supporting
confidence: 54%
“…In the multiple regression analysis, CA-125 was independently associated with RV dilatation, pericardial effusion and left ventricular EF. Though, there were few reports in the literature mentioning such possible association between CA-125 level and right heart chambers [14,15], there was no study showing that relationship in those without depressed EF and demonstrating such independent relationship of these parameters influencing plasma levels of CA-125 in a group of all comers. Mechanical stress on the venous system up on decreased unloading effect of RV, inflammatory stimuli involving pulmonary bed could all be potential sources of explanation such effect.…”
Section: Discussionmentioning
confidence: 95%
“…Besides, RV dilatation and tricuspid regurgitation were not separated from other potential confounders. Actually, potential role of right side of the heart in the plasma levels of CA-125 has not been searched in detail so far except case reports [15][16]. In a very recent study enrolling all comers, it was shown that presence of depressed ejection fraction, presence of right ventricular dilatation and presence of pericardial effusion were independent predictors of high CA-125 levels [17] further supporting the notion that RV dilatation could be responsible for elevations of CA-125.…”
Section: Discussionmentioning
confidence: 99%